Choose Your Own Adventure! An empirical study on gamification of postgraduate learning on research project design - Daisy Abbott (Journal of Play in Adulthood, 2024)
It is difficult to teach complex topics such as academic research to student cohorts who are widely heterogeneous in prior knowledge, learning goals, and learning preferences. Exploratory, quest-like approaches show promise for increasing engagement, personalization, and autonomy, however, there is a lack of empirical data on which, if any, aspects of gamification can benefit learning. This paper presents analytics and qualitative responses to a Choose Your Own Adventure for postgraduate design of research projects. It focusses on non-linear navigation for self-directed personalization, digital badges, and the role of narrative within a gamified learning tool. Results highlight high user attrition, effective personalization of learning, high acceptance of gamification approaches, and much lower interest in some gamification elements, contributing value to the pedagogy of learning and teaching research skills.